Reconstruction on The Regulations of Advocate Organizational System as Accountability for The Quality of Professions - Lusia Sulastri; Norcha Satria Adi Nugroho (Faculty of Law, Universitas Jenderal Soedirman, 2020)
Historically the organizational system experienced various advocate conflicts. This study aims to review and analyse the dynamics and the weaknesses on the regulation of advocate organizations system, and to formulate the reconstruction of the implementation of the advocate organization system as an accountability for the quality of a profession based on the value of justice. The results of the study indicate that, initially, the advocate organizational system as a single bar association leads to multi bar association. Among the weaknesses on the regulation of advocate organizations are the lack of a solid advocate organization, compulsion to establish new advocate organization, a judicial intervention in the administration of an advocate's oath, commercialization of special education for advocate without any standardized curriculum and test. Reconstruction is necessary in order to increase accountability for the quality of the profession based on the value of justice.